2010
DOI: 10.1007/s11136-010-9601-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of quality of life to dispositional optimism, health locus of control and self-efficacy in older subjects living in different environments

Abstract: Data of this cross-sectional study suggests that the veteran home elderly, as a group 'in transition' between community and institution, should be the first target of psychological preventive and health-promoting measures aimed at improving QOL in older population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
99
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 49 publications
12
99
2
Order By: Relevance
“…7 Furthermore, an individual's perception and establishment of goals and expectations are undoubtedly influenced by personal characteristics such as optimism, psychic stability, and confidence. 36 Not only were mental and personality functions identified as powerful determinants of HRQoL already in previous studies, [37][38][39] but the relationship between HRQoL and gait as well as activities of daily living (ADL), including housework, were also identified as determinants. 40,41 This association was in the chronic phase after stroke.…”
Section: Discussionmentioning
confidence: 96%
“…7 Furthermore, an individual's perception and establishment of goals and expectations are undoubtedly influenced by personal characteristics such as optimism, psychic stability, and confidence. 36 Not only were mental and personality functions identified as powerful determinants of HRQoL already in previous studies, [37][38][39] but the relationship between HRQoL and gait as well as activities of daily living (ADL), including housework, were also identified as determinants. 40,41 This association was in the chronic phase after stroke.…”
Section: Discussionmentioning
confidence: 96%
“…The well-known relationships between optimism and other healthy characteristics such as higher quality of life (Kostka & Jachimowicz, 2010), well-being (He et al, 2013), life satisfaction (Extremera et al, 2009;Jiang et al, 2014), emotional intelligence (Extremera et al, 2009), less drug consumption (Hamvai & Piko, 2010) and psychological problems (Sánchez-Hernández et al, 2010), combined with the new association with circadian typology, underline the morning-type as a healthier typology which could be considered as a protective factor for the development of psychological problems. By contrast, the evening-type could be considered as a risk factor, especially for the development of mood and substance use disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the relationship between optimism and sex have found marginal or absent differences (Herzberg et al, 2006;Zenger et al, 2013). To date is well established that optimism is strongly related to quality of life (Kostka & Jachimowicz, 2010), well-being (He et al, 2013), life satisfaction (Extremera et al, 2009;Jiang et al, 2014), coping strategies (Nes & Segerstrom, 2006), emotional intelligence (Extremera et al, 2009), substance use (Hamvai & Piko, 2010) and to several psychological problems (Sánchez-Hernández et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…the "self") factors influence health [17]. HLC has been associated with quality of life, subjective sense of well-being, psychological well-being and health-related behaviors such as diet and smoking [18-23]. As such, HLC seems to be a key element of general health and well-being that deserves to be investigated in different population settings.…”
Section: Introductionmentioning
confidence: 99%